2001
DOI: 10.1016/s0076-6879(01)34476-2
|View full text |Cite
|
Sign up to set email alerts
|

[24] Assaying activity and assessing thermostability of hyperthermophilic enzymes

Abstract: There is now a wide variety of intra-and extra-cellular enzymes available from organisms growing above 75°C, and having sufficient stability to allow assay well above this temperature. For some of these enzymes, to assay below even 95°C will involve measurement below the optimal growth temperature for the organism. The purpose of this chapter is to cover practical aspects of enzyme assay procedures that are specific to high temperatures. Since by far the commonest routine assessment of enzyme stability is acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…The temperature dependence and the apparent T opt principally depend on the procedures used to assay enzymatic activity (buffers, heat rate and incubation times, thermostability of the substrate etc. ; see for example [53]). However, temperaturedependent activity plots with data taken from the literature allow at least a qualitative comparison (see fig.…”
Section: Temperature Dependence Of Enzymatic Activitymentioning
confidence: 98%
“…The temperature dependence and the apparent T opt principally depend on the procedures used to assay enzymatic activity (buffers, heat rate and incubation times, thermostability of the substrate etc. ; see for example [53]). However, temperaturedependent activity plots with data taken from the literature allow at least a qualitative comparison (see fig.…”
Section: Temperature Dependence Of Enzymatic Activitymentioning
confidence: 98%
“…One use of these measurements is to determine the temperature of maximal enzyme activity, which is an important parameter in characterizing the thermal adaptation process (Fitter et al 2001;D'Amico et al 2003). The temperature dependence and the apparent T opt principally depend on the procedures used to assay enzyme activity (Daniel and Danson 2001). However, temperature-dependent activity plots with data taken from the literature allow at least a qualitative comparison (Fitter 2005).…”
Section: Resultsmentioning
confidence: 99%
“…• C, and since few continuous assay methods are practical at such temperatures, most such assays will have to be discontinuous [4]. Finally, we have demonstrated that the use of initial, zero-time rates enables the ready determination of the Equilibrium Model parameters (except G ‡ inact ) of most non-ideal enzyme reactions.…”
Section: Discussionmentioning
confidence: 97%
“…Assays at high temperature (and over any wide temperature range) can sometimes pose special problems and may need additional care [4][5][6]. Quartz cuvettes were used in all experiments for their relatively quick temperature equilibration and heat-retaining capacity.…”
Section: Assay Conditionsmentioning
confidence: 99%